Protein C Osaka 10 with Aberrant Propeptide Processing: Loss of Anticoagulant Activity Due to an Amino Acid Substitution in the Protein C Precursor - Miyata, Toshiyuki; Zheng, Yan-Zhen; Sakata, Toshiyuki; Kato, Hisao (Thrombosis and Haemostasis, 1995)
We studied the molecular basis of protein C deficiency in a family with a history of thromboembolic disease. An approximately 50% reduction in anticoagulant activity despite normal levels of protein C amidolytic activity and antigen was detected in plasma from the proband. All the exons and intron/exon junctions of the protein C gene were studied using a strategy that combined polymerase chain reaction amplification with DNA sequencing of the amplified fragments. We identified a C-to-A change at nucleotide number 1387 of the protein C gene in the proband and his mother, and this mutant was designated protein C Osaka 10. The C-to-A change resulted in the substitution of Ser for Arg at position -1, which is the processing protease cleavage site. The mutant protein C was partially purified from plasma of the patient’s mother using barium adsorption followed by ion-exchange column chromatography. It eluted at the same sodium chloride concentration as normal protein C, and thus γ-carboxylation of the mutant protein appeared to be normal. The apparent molecular weight of this mutant protein C was the same as that of the normal protein on immunoblotting. Amino-terminal sequence analysis showed that the light chain of the mutant protein C had an additional Ser at position -1. Thus, the loss of anticoagulant activity of protein C Osaka 10 can be explained by alteration of the conformation of the Gla domain by the additional Ser in the mutant molecule.